FAKTOR INTERNAL DAN FAKTOR EKSTERNAL YANG MEMPENGARUHI AUDITOR DALAM PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Inayatus Sholekhah, 13.05.52.0196; Himmawan, Arief (Students Journal of Accounting and Banking, 2017)
Many auditors who perform actions on premature termination of audit procedures, resulting in reduced quality of the audit. Though the information of the results of the audit is required by the entity to get an investor. Rhode (1978) conducted a survey of senior auditor of public accounting firms in six major Irish and showed that 89 percent of respondents reported having some form of audit quality reduction behavior. The population in this study is the auditor who works at KAP in Semarang, Solo, and Yogyakarta (DIY). Sampling was done by purposive sampling technique and the total sample of 62 respondents. Methods of collecting primary data by spreading the questionnaire. The results of this study that partially Locus Of Control, Turnover Intentions, Time Pressure, Audit Risk, and Materialitas has a positive and significant impact on the premature termination of audit procedures. Professional Commitment and Review Procedure And Quality Control has no effect on the premature termination of audit procedures.Keywords: Locus Of Control, Turnover Intentions, Time Pressure, Audit Risk, Professional Commitment, Review Procedure and Quality Control, Materiality, and Premature Termination of The Audit Procedures